Moderation of Homosexual Fiqh in Indonesia: A Study of The Huzaemah Tahido Yanggo’s thought - Ariyadi, Ariyadi; Muzainah, Gusti; Setiawan, Alfiandri; Islamy, Athoillah; Susilo, Adib (AL-ISTINBATH : Jurnal Hukum Islam, 2022)
This study aims to identify the moderation of Huzaemah Tahido Yanggo's fiqh of the law of purity over homosexual acts. This is a qualitative research in the form of heirloom studies which uses a normative-philosophical approach. The paradigm of moderate fiqh conceptualized by M. Quraish Shihab becomes the theory of analysis. The results show that there is a paradigm basis for moderate fiqh in the construction of Huzaemah's fiqh on the law of purity over homosexual acts. This great conclusion can be seen from the following various aspects. The first aspect is the dimensions of the paradigm of fiqh al-maqashid and fiqh al-awlawiyat in the use of theological foundations that emphasize the realization of the benefit orientation of Islamic sharia, namely the regeneration of offspring (hifz al-nasl) and the protection of honor (hifz al-'ird). The second aspect is the paradigm pattern of fiqh al-muwazanat, and fiqh al-ma'alat in the basis of consideration of the impact of disease from a medical perspective, and violations of national legal norms in Indonesia. The pattern of the fiqh al-ma'alat paradigm can also be seen from Huzaemah's advice to the community and the government to realize preventive efforts, healing as well as rehabilitation and empowerment of homosexual actors to positive things. The theoretical implications of this study show that a holistic fiqh paradigm is needed in prohibiting homosexual acts, namely by involving multiple perspectives, such as medical, state norms, psychology and socio-cultural norms.